Komoditas Unggulan dan Daya Saing Sektor Pertanian di Kabupaten Sijunjung - Syahrial Syahrial; Pebry Aldy Saputra; Alvindo Dermawan (AGRIMOR, 2023)
Sijunjung Regency, the agricultural sector is the main driver of increasing regional gross regional product. This study aims to examine the leading commodity and the trend of leading commodities in the future in Sijunjung Regency. This research was conducted in Sijunjung Regency, West Sumatra Province. Location Quotient, Specialization Kousien, Localition Kousien, Shift Share Analysis, and Dynamic Location Quotient are analytical techniques used. The results of the analysis show that the leading commodities in the agricultural sector are rice, mango, durian, banana and rubber then the district and province competitiveness is equally strong in both regions and some of the leading commodities experience localization and specialization in Sijunjung district. This research is expected to encourage local governments to adopt land use policies to optimize progress in the agricultural sector.